If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5x + -2 = 9x + -38 Reorder the terms: -2 + 5x = 9x + -38 Reorder the terms: -2 + 5x = -38 + 9x Solving -2 + 5x = -38 + 9x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-9x' to each side of the equation. -2 + 5x + -9x = -38 + 9x + -9x Combine like terms: 5x + -9x = -4x -2 + -4x = -38 + 9x + -9x Combine like terms: 9x + -9x = 0 -2 + -4x = -38 + 0 -2 + -4x = -38 Add '2' to each side of the equation. -2 + 2 + -4x = -38 + 2 Combine like terms: -2 + 2 = 0 0 + -4x = -38 + 2 -4x = -38 + 2 Combine like terms: -38 + 2 = -36 -4x = -36 Divide each side by '-4'. x = 9 Simplifying x = 9
| P^2-q^2=48 | | 9x-6=18+6x | | 8x+8=7x+12 | | x^2+11x+22= | | -16+8x+8k-5x-5k+9= | | -2(12-9y)+y=5(y-2) | | 13p-10=23 | | 5X+5(7X-13)=175 | | n+n+n=278 | | 5(y+17)=6(y+14) | | X-11=4x+1 | | 2a+3c=40.25 | | 204/323= | | 3(y+5)-8y= | | 1/4(12x-20)=1/5(25x-15) | | 9x+9.02=7x+13 | | 0.5x+11.9=x-2.25 | | x^2+6x=9-x | | .06x-.03=.06x+.01 | | 4e^2x-3=100 | | 2t(t-1)=60 | | X(-9-1)=4(x+7) | | 2x-1+x+3= | | f(x)=tan^1(sin(4x)) | | 7(6+x)=2x-3 | | 3(w+6)=42 | | 4x^2+10x=3x^2-25 | | 8x-5=28 | | 5(x+5)-5x=19 | | 2(x+2)=-2(4x+2) | | 5m^2+32m=-12 | | 4x-19=3x-10 |